PENGARUH PROMOSI KESEHATAN TENTANG BREAST CARE TERHADAP PENGETAHUAN IBU HAMIL PRIMIGRAVIDA DI WILAYAH KERJA PUSKESMAS PASIR NANGKA - Tasya Tjahyaningsih (2023)
Breast care has many benefits for pregnant women to increase milk productivity and milk expenditure. However, most primigravida pregnant women do not know the importance of breast care, this is caused by a lack of information about breast care. The purpose of this study was to determine the effect of health promotion regarding breast care on the knowledge of primigravida pregnant women in the Pasir Nangka Public Health Center working area which was carried out in March-June 2023. This research used a quasi-experimental method with a pretest-posttest two group design with phantom media and leaflets. Samples were taken by purposive sampling technique totaling 104 primigravida pregnant women. Data analysis with Wilcoxon and Mann Whitney test. The results of the analysis of data on the characteristics of the majority of respondents 75% of the experimental group and 69% of the control group were aged 21-35, the two groups were mostly housewives 85% of the experimental group and 77% of the control group, 86% and 85% on average earning less than or equal to the Tangerang District Minimum Wage in the experimental group and the control group, both groups had the senior hight school. The results of bivariate analysis using the Wilcoxon test showed that there was an effect of knowledge about breast care on primigravida pregnant women before and after health promotion (p value 0.000). There are differences in the effectiveness of health promotion regarding breast care through phantom media and leaflets. (p-value 0.000). So it can be concluded that there is an effect of breast care health promotion on the knowledge of primigravida pregnant women and there is a difference in effectiveness between phantom media and leaflet media. Breast care health promotion with phantom media is more effective than leaflet media. Suggestions for giving or delivering breast care material in pregnant women's classes use phantom media and attractive leaflets for health promotion media.